Rational Type Contraction in Consideration of Fixed-Point Theorems in B-Metric Spaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we prove common fixed-point theorems in complete b-metric spaces using rational type contraction for two self-mappings. Our result improves and extends the results proved by Mlaiki et al. [1] for a single continuous self-mapping in extended complete bmetric space. We improve the results of Mlaiki et al. [1] to complete b-metric spaces for two self-mappings without assuming the continuity of any mapping